The Chinese-Indonesian collections in the National Museum of World Cultures, the Netherlands - Brinkgreve, Francine (UI Scholars Hub, 2017)
Among the more than 130,000 objects from Indonesia in the Dutch National Museum of World Cultures, many once belonged to or were used by the Chinese population of Indonesia. In this article, the authors provide an overview of these collections by presenting their collecting histories from the earliest acquisitions to the most recent collections and by highlighting a number of objects, which in their materials, techniques, motifs, colours or function show a combination of elements from both Chinese and Indonesian cultures. The authors pay particular attention to objects which play a role in the Chinese-Indonesian wedding ceremony.